Media Framing of “Ultimatum, No Thanks” Protests in North Macedonia: Analyzing Nationalist Confrontation and Ethnic Solidarity Frames - Samet Yerköy (Türkiye İletişim Araştırmaları Dergisi)
This article examines the media framing of the demonstrations in North Macedonia’s capital againstthe French proposal aimed at resolving the country’s dispute with Bulgaria and initiating EU accessiontalks. The protests, held from July 2, 2022 to July 16, 2022 under the slogan “Ultimatum, No Thanks,”reflected widespread opposition to the proposal, which many saw as detrimental to Macedonian nationalinterests. Through a qualitative analysis of media coverage, specifically focusing on online media outlets,the study explores how different frames, such as Nationalist Confrontation and Ethnic Solidarity, shapedpublic discourse and perceptions of the protests. The government’s portrayal of the proposal as protectingthe Macedonian language and identity contrasts sharply with the opposition’s view of it as leading tothe ‘Bulgarization’ of the nation. This research fills a crucial gap in understanding the interplay betweenidentity politics, diplomatic negotiations, and media representation in times of high political tension. Theissue remains highly relevant today as it continues to be a significant obstacle to North Macedonia’s EUaccession. The findings suggest that media framing significantly influences public opinion and politicaloutcomes. Furthermore, the study highlights the broader implications for interethnic relations in theWestern Balkans and the ongoing EU accession processes.